Xanthigen attenuates high-fat diet-induced obesity through down-regulation of PPARγ and activation of the AMPK pathway - Choi, Kyeong-Mi; Jeon, Young Soo; Kim, Wonkyun; Lee, Anna; Kim, Yong-Gil; Lee, Ju Hyun; Kang, Young Eun; Jung, Jae-Chul; Lee, Jeongrai; Min, Bokkee; Kwon, Suk Hyung; Davis, Barbara; et al. (Food science and biotechnology, 2014)
Xanthigen, a mixture of brown seaweed and pomegranate seed extracts, has weight loss properties and lipid-lowering effects in mice and humans. This study elucidated the Xanthigen mechanism of an anti-obesity activity in high-fat diet (HFD)-fed mice. Xanthigen decreased expression of peroxisome proliferator-activated receptor γ (PPARγ) in the adipose tissue of HFD-fed mice. The serum leptin level and the adipose tissue leptin expression in mice fed HFD plus Xanthigen were significantly decreased, compared to HFD-fed mice. Phosphorylation of AMPactivated protein kinase (AMPK) α and β and acetyl-CoA carboxylase (ACC) in the adipose tissue of HFD plus Xanthigen-fed mice was elevated, and HMG-CoA reductase (HMGCR) expression was decreased. Xanthigen may have an anti-obesity activity by down-regulation of PPARγ and activation of the AMPK pathway.